The Drosophila saxophone gene: a serine-threonine kinase receptor of the TGF- superfamily. - Xie, T.; Finelli, A.; Padgett, R.W. (Science, 1994)
The Drosophila decapentaplegic (dpp) gene encodes a transforming growth factor-beta (TGF-beta)-like protein that plays a key role in several aspects of development. Transduction of the DPP signal was investigated by cloning of serine-threonine kinase transmembrane receptors from Drosophila because this type of receptor is specific for the TGF-beta-like ligands. Here evidence is provided demonstrating that the Drosophila saxophone (sax) gene, a previously identified female sterile locus, encodes a TGF-beta-like type I receptor. Embryos from sax mothers and dpp embryos exhibit similar mutant phenotypes during early gastrulation, and these two loci exhibit genetic interactions, which suggest that they are utilized in the same pathway. These data suggest that sax encodes a receptor for dpp.